Russian Accounting in the 17th Century: Details on the Production and Sales of Alcoholic Beverages - Svetlana N. KARELSKAIA; Ekaterina I. ZUGA (Communications of International Proceedings, 2020)
In this research authors described the development of accounting for production and sales of alcoholic beverages in Russia in the 17th century. By this time, it had provided a framework for the emergence of a complex accounting system based on principles different from traditional double entry accounting. Authors presented in detail the accounting system applied in Russia before the advent of double entry accounting and successfully performed the specific tasks set before it.
Keywords: Accounting; state revenue; alcoholic beverages; ledger.